Live-Work Interior Quality for Older People in Low-Income Housing in Bangkok - Sattayakorn, Sutida; Sinuraibhan, Soranart; Ramasoot, Saithiwa; Wungpatcharapon, Supreeya; Hadjri, Karim; Durosaiye, Isaiah; Huang, Junji (Interiority, 2023)
This study explores to determine the live-work housing needs of low-income older people in informal settlements, the ways of life of whom contemporary housing provision often fails to consider. A questionnaire survey was conducted in three communities in Klong Toey, the largest informal settlement in Bangkok, to understand households’ satisfaction levels and expectations regarding the interior quality of their live-work housing. Older people’s specific interior spaces and housing requirements and expectations vary depending on the nature of their livelihood activities that can be categorised into three main groups, namely service, cook, and stock. The findings suggest a strong relationship between housing domains and the overall satisfaction of older people. There is a strong relationship between overall housing satisfaction and comfort in interior living spaces, as well as safety for domestic working spaces. Design, Health, Comfort, and Adaptability are important domains for live-work environments that ensure housing meets older people’s expectations. Therefore, housing design and improvements should embrace the live-work concept to maintain a sustainable and healthy ageing environment.